Evaluation of the Knowledge and Performance of Nursing Students Regarding EvidenceBased Care - Parvin Mangolian Shahrbabaki; Jamileh Farokhzadian; Esmat Nouhi (Kerman University of Medical Sciences, 2016)
Background & Objective: In recent years evidencebased care has been recognized as one of the essential competencies of nursing graduates Since senior nursing students are on the verge of graduating studying factors affective on the use of evidencebased care in their professional future and emphasis on educational programming to strengthen this competency are necessary This study aimed to evaluate the knowledge and performance of senior nursing students regarding evidencebased care Methods: The present descriptiveanalytical study was conducted on 43 senior nursing students of Kerman University of Medical Sciences Iran in 2015 Data were collected using the Persian version of the Nursing Students Knowledge and Performance about EvidenceBased Practice Questionnaire Data were analyzed using descriptive statistics (percentage mean and standard deviation) and analytical statistics (Pearson correlation coefficient ANOVA) in SPSS software Results: The results indicated that the majority of students (535%) had sufficient knowledge of evidencebased care The total mean score of knowledge of the students was 1225 ± 334 while the majority of students (512%) showed poor performance The total mean score of performance of the students was 1728 ± 785 There was a direct correlation between knowledge and performance of the students (r < 056) Conclusion: There is gap between the knowledge and performance of students regarding evidencebased care; despite their sufficient knowledge on evidencebased care their performance was poor It is suggested that a suitable milieu for promoting evidencebased care is provided and theory and practice are linked through suitable planning a review of the curriculum and creating an appropriate educational environment for nursing students as future nurses